Comparative Analysis of CBS and Non-CBS Brake Efficiency with Variations in Load and Road Pavement Construction - Anugrah Fauzandy; Setya Wijayanta (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
The development of transportation, especially the use of motorcycles has contributed significantly to increasing community mobility. However, along with the increasing number of vehicles, the risk of traffic accidents has also increased. One of the main factors causing accidents is the failure of the braking system, which most often occurs in two-wheeled vehicles. Automatic motorcycles, which generally still use conventional braking systems, have a higher level of vulnerability to brake failure compared to other types of vehicles. The ease of use of automatic motorcycles makes this vehicle the main choice for people in their daily activities. One of the braking system technologies developed by motorcycle manufacturers in Indonesia is the Combi Brake System (CBS), which aims to improve the safety of motorcycle riders. This study aims to analyze the comparison of braking efficiency between the CBS and Non-CBS systems by considering variations in load and type of road pavement construction. The research method uses an experimental approach with the road brake test method at speeds of 40 km/h and 60 km/h. The test results showed that the highest brake efficiency of 56.76% occurred on asphalt roads with active CBS brakes and a load of 65 kg at a speed of 60 km/h, while the lowest efficiency of 23.28% occurred on concrete roads with inactive CBS brakes and a load of 125 kg at a speed of 40 km/h. . While the brake temperature analysis showed the highest value of 79.34 °C on asphalt roads with CBS brakes off and 125 kg load at 60 km/h speed, while the lowest temperature of 48.36 °C occurred on concrete roads with CBS brakes on and 65 kg load at 40 km/h speed.